Gratitude (shukr) and Benevolence (ihsān) to Parents in Tafsir Quraish Shihab: The Relevance of Qur'anic Values for Instant Cultural Generations - Tika Erpiani; Mardian Idris Harahap (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to examine the Qur’anic values of gratitude (shukr) and benevolence (ihsān) toward parents as interpreted by M. Quraish Shihab in his Tafsir al-Misbah, using a thematic exegesis (al-tafsīr al-mawḍū‘ī) approach. The analysis focuses on Surah al-Isrā’ [17]:23–24, which links filial piety (birr al-wālidayn) directly to the principle of monotheism (tawḥīd). By centering the interpretation of Quraish Shihab and contextualizing it within the sociocultural framework of the instant-gratification generation marked by individualism, speed, and emotional detachment. This study is a qualitative study based on library research using the thematic interpretation approach (al-tafsīr al-mawḍū‘ī). The main data were obtained from authoritative interpretation books that were selected purposively because they represent classical and contemporary styles. And applying data triangulation through comparative reading between interpretations and adjustments to empirical findings from sociological and nursing studies on the elderly. This study also adopts the perspective of Jean Watson's Human Caring Theory as an analytical complement to dialogue between Qur'anic values ​​and ethical-spiritual approaches in care. This study explores the contemporary relevance of Qur’anic ethics in strengthening intergenerational ties and elderly care practices. The findings indicate that shukr and ihsān are not merely ethical acts but profound spiritual expressions of faith that must be revitalized in the lived experience of today’s youth. In the context of aging parents, care is viewed as a spiritual devotion that reflects emotional maturity, social responsibility, and personal righteousness. The study also integrates Jean Watson’s Human Caring theory to highlight the compatibility between Islamic spiritual values and holistic caregiving models in modern Muslim families.